(3PNQ GdeYGO Ydi hRf HGfJ SYGOs - (3eMeO Hf SYjO Hf MeGO Hf YHO Gddg GdUfgGLj GdHhUjQj GdeUQj, TQa GdOjf, CHh YHO Gddg , (B696 (3g` s; (3cYH Hf RgjQ , CHh GdeZQH,J (B26 (3g` s
(3ChdgG (B:s
(3bGd GdHhUjQj QMeg Gddg JYGdi hQVi Yfg(B: (3Edi eJi CfJ HGddPGJ eTZhd hCfJ Yf cd bOeJ eSFhd s
(3BNQgG (B:s
(3eG dGM VhA UHGM hGSJSqQ Hg ef GdchGcH bfOjd abfOjd s
(3Vef eLehY , JQJjHgG (B: (3ef U (B296 - (3U(B309s
(3aj cTa GdXfhf(B: (3PNQ GdeYGO aj oeYGQVI HGfJ SYGOs
(3gj bUjOI YGQV HgG bUjOI cYH Hf RgjQ (B"(3HGfJ SYGO(B"s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B226s
Keywords: (3GdCOHs